The Hb H Disease Genotypes in Southern China. (February 2014) - Fang, Jianpei; Chen, Luming; Zeng, Ruiping; Tian, Qiuhong; Jiang, Weiying; Li, Hongyi; Chen, Zheng; Du, Chuanshu; Chen, Suqin
Abstract We report the genetic data of 435 patients with Hb H (β4) disease who presented at our center between 2005 and 2012. Our results showed that all patients had the Southeast Asian deletion (– –SEA) on one allele. The –α3.7 (rightward) deletion was the most common on the other allele, followed by the –α4.2 (leftward) deletion, Hb Constant Spring (Hb CS, α142, Term → Gln; HBA2: c.427T > C) and Hb Quong Sze [Hb QS, α125(H8)Leu → Pro; HBA2: c.377T > C] mutations. Two rare point mutations, α31(B12)Arg → Lys; HBA2: c.95G > A and Hb Zurich Albisrieden [α59(E8)Gly → Arg; HBA1: c.178G > C], were also identified. Four patients had a concomitant β-thalassemia (β-thal) heterozygosity. Our results reflect the genetic heterogeneity of Hb H disease and the interaction between Hb H disease and β-thal trait in Southern China.